1979
DOI: 10.2307/2327051
|View full text |Cite
|
Sign up to set email alerts
|

Equity Rights Issues and the Efficiency of the UK Stock Market

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
69
0
6

Year Published

1979
1979
2009
2009

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(78 citation statements)
references
References 20 publications
3
69
0
6
Order By: Relevance
“…As some of the companies in the sample are subject to infrequent trading (perhaps due to their fairly small size (see Table 1)), we apply the trade-to-trade approach to calculate the CAR (Marsh, 1979;Dimson, 1979). The tradeto-trade approach is an adjusted form of the market model.…”
Section: Methodsmentioning
confidence: 99%
“…As some of the companies in the sample are subject to infrequent trading (perhaps due to their fairly small size (see Table 1)), we apply the trade-to-trade approach to calculate the CAR (Marsh, 1979;Dimson, 1979). The tradeto-trade approach is an adjusted form of the market model.…”
Section: Methodsmentioning
confidence: 99%
“…In contrast to the US, where most SEOs are conducted through the use of cash offers, UK companies in past decades predominantly 1 raised new equity by making rights issues (Armitage, 1998;Levis, 1995;Marsh, 1979;Slovin, Sushka, & Lai, 2000). This method allows companies to protect existing shareholders by avoiding the potential dilution of their wealth and loss of control following an equity issue.…”
Section: Theoretical Background and Empirical Evidencementioning
confidence: 99%
“…In a study testing the price pressure hypothesis for UK data, Marsh (1979) produced evidence of post-SEO positive abnormal returns. Using a dataset consisting of the entire population of UK rights issues for the period 1962-1975, the author concluded that his results are in favour of semi-strong form efficiency and can be attributed to a small size effect rather than the SEOs' announcements (Marsh, 1979, pp.…”
Section: Theoretical Background and Empirical Evidencementioning
confidence: 99%
“…In this s and indirect tests to identify ly caused the decrease in v Supply Effect. A possible cess returns pattern observe pressure hypothesis discus [10], and recently, by Asq hypothesis asserts that ne supply/demand imbalance shares to be sold at a discou discount is a positive functi Equity for debt exchanges h to secondary distributions; '4 shares did cause a supply im '1Scholes reported the average pro sample to be 0.0216; the average pro sample was 0.021. Marsh found evidence to support the existence of a '5Copeland and Weston [4], p. 327, discuss the price pressure hypothesis, and present diagrams representing the shape of CPE patterns when price pressure exists.…”
Section: Analysis Of the Resultsmentioning
confidence: 97%